Enterobacteria in the 21st century: a review focused on taxonomic changes - Morales-López, Soraya; Yepes, Jayr A; Prada-Herrera, Juan C; Torres-Jiménez, Augusto (The Journal of Infection in Developing Countries, 2019)
Introduction: Enterobacteria are the main group causing infections in humans. The aim of this review is to present the new genera and the taxonomic changes that the Enterobacteriacea family has experienced in recent years. Methodology: a systematic search of papers published in databases from January 2000 to July 2018 was done. Additionally, the bibliographic references of each document were reviewed and each paper citing the article was reviewed in search of clinical cases. Results: Nineteen new genera of Enterobacteria have been described since 2000. The genera Yersinia, Morganella and Erwinia do not belong to the family Enterobacteriacea anymore. Conclusions: for an adequate clinical and epidemiological interpretation, it is advisable to update the libraries of the commercial systems used for the identification of the microorganisms, as well as to train the staff in the taxonomic changes of microorganisms.